2014
DOI: 10.5433/1679-0359.2014v35n4suplp2767
|View full text |Cite
|
Sign up to set email alerts
|

Digestibilidade do grão de trigo de duplo propósito, cultivar BRS Tarumã, produzido em sistema agroecológico ou convencional para suínos

Abstract: ResumoForam conduzidos três ensaios de digestibilidade para determinar o valor nutricional, os coeficientes de digestibilidade aparente e os teores de energia do trigo de duplo propósito (cultivar BRS Tarumã), produzido em sistema agroecológico ou convencional, para suínos em diferentes fases da criação (15, 45 e 75 kg de peso vivo-PV). Foram utilizados 15 suínos machos castrados, híbridos comerciais de alto desempenho para cada fase, divididos em três grupos experimentais, o primeiro recebeu uma ração específ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For the BRS Pastoreio cultivar, the highest protein content was found when it was submitted to two cuts and without the N addition, attaining values of around 18%, with the Pastoreio cultivar mean protein content being 13.2%, according to studies by Castro et al (2016). This shows that genotypes present differences in their response to this fertilization and in relation to the mean protein levels, since the BRS Tarumã cultivar has commonly presented about 17.7% protein in other studies (Paiano et al, 2014). For this study, the maximum mean contents were of about 16.5%.…”
Section: /7mentioning
confidence: 47%
“…For the BRS Pastoreio cultivar, the highest protein content was found when it was submitted to two cuts and without the N addition, attaining values of around 18%, with the Pastoreio cultivar mean protein content being 13.2%, according to studies by Castro et al (2016). This shows that genotypes present differences in their response to this fertilization and in relation to the mean protein levels, since the BRS Tarumã cultivar has commonly presented about 17.7% protein in other studies (Paiano et al, 2014). For this study, the maximum mean contents were of about 16.5%.…”
Section: /7mentioning
confidence: 47%
“…Comparing conventional wheat grain production systems (chemical fertilizer) and agro ecological (swine manure) on crop-livestock integration system in Santa Catarina Paiano et al (2014) found that 1,000 BRS Tarumã ® grains weighed around 24 grams and test weight (TW) obtained was more than 74 grams. The determination of TW lets you sort the wheat grains into three categories, according to rules published by the Ministério da Agricultura (BRASIL, 2001): Type 1 with a minimum 78 of TW, Type 2 with a minimum of 75 of TW and Type 3 with a minimum 70 of TW.…”
Section: Resultsmentioning
confidence: 99%